Effect of gratitude on health behaviour : two weeks of counting blessings on food portion selection - Ng, Xue Qi (2019)
Prior studies have suggested the influence of gratitude on health-related behaviours. However, gratitude and eating behaviours have yet to be studied thoroughly. Recent studies have shown that individuals’ subjective experiences may affect eating behaviour. Specifically, perceived deprivation, feelings of being at a disadvantage compared to others, resulted in the selection of larger food portion size and greater caloric intake. Given that feelings of deprivation stimulate appetite, this study tested whether gratitude would reverse the effect of deprivation and reduce intended food consumption and intake. Health-related behaviours such as physical activity and sleep were also examined. The present study involved two experimental conditions – gratitude and control. For two weeks, 193 participants kept diary and food journals and completed pre and post lab visits. Participants in the gratitude condition listed things they were grateful for every night, while the control group listed events that occurred. Repeated measures ANOVA showed that the gratitude condition resulted in a post- intervention decrease in portion size selection for a variety of food items among males, controlling for attitudes towards diary writing. Changes in deprivation levels and improved perceived social status were also found after two weeks. These findings supported the link between resource insecurity and appetite, whereby feelings of gratefulness (i.e. focus on important resources and opportunities that were satisfied) may have made individuals perceive less resource inadequacies, and reduced their intended appetite. Gratitude interventions, which are simple and easy to implement, may confer health-related benefits. This has implications on strategies to promote healthy living.